On the structure of the lower crust to mantle transition beneath an accretionary inherited Andean margin, northwestern Andes (2022)
The crust-mantle transition beneath the northwestern Andes is expected to be complex given its accretionary tectonic history. Considering that research on this matter remains scarce, especially in the Colombian region, this thesis presents new insights into the structure and nature of the crust-mantle transition in several parts of the orogen. Four chapters are presented, discussing: (1) variations in Moho depth along the orogen using inversion of gravity data; (2) latitudinal heterogeneity and anisotropy in the uppermost mantle beneath the modern arc using Pn and Sn wave speed estimates, and thermo-compositional modeling; (3) the nature of the arc root beneath the modern arc by means of a receiver function analysis; and (4) intra-continental deformation beneath the Eastern Cordillera plateau from a joint inversion of arrival times of local earthquakes and gravity data. Integrated results suggest three main features associated with a thickened crust: along the northwestern foreland region (influenced by the adjacent thickened Eastern Cordillera), along the axis of the Eastern Cordillera (related to its shortening history and magmatic additions), and in the southern part of the modern arc, in the Andes of southern Colombia and northern Ecuador (likely a combined result of mafic addition to the base of the crust, foundering tectonics, and lateral displacement of the lower crust). Investigations on the upper mantle beneath the modern arc suggest a well-developed anisotropy, showing a latitudinal dissimilarity in wave speeds and temperature. The northern part (north of 4°N; <75 km wide arc) is seismically slower, and has a higher degree of anisotropy, suggesting warmer conditions. The southern part (south of 2°N; >120 km wide arc) is faster, less anisotropic, and consistent with a colder state. Beneath the volcanic gap region (2°-4°N), seismic speeds are similar to those in the north, yet a colder thermal state is suggested. The controlling factor of the anisotropy is the preferred orientation of olivine and pyroxene. Latitudinal anisotropy and temperature dissimilarities are likely influenced by the Caldas tear to the north, prompting hot mantle influx, and the Carnegie ridge interaction to the south, prompting shallower subduction. Additional investigations on the arc domain, using the teleseismic receiver function technique, which looks for P to S phase conversions, indicate that the crustal root beneath the arc is characterized by high velocities and a latitudinally variable thickness, which coupled with documented xenoliths supports an arclogite nature. This high-velocity and high-density arc root suggest an offset between the seismic Moho and the crust-mantle boundary of around 8.5-14 km. Finally, beneath the Eastern Cordillera plateau, a well-imaged anomaly is identified at depths of 40-60 km beneath the western flank of the plateau, at a latitude of ~5.7°N. The slow velocity anomaly is interpreted as crustal materials eastwardly underthrusting beneath the western flank. This process is thought to be prompting the abrupt change in topography between the adjacent low-elevated basin and the orogenic plateau. This thesis shows how the crust-mantle transition along the northwestern Andes follows the idea that a heterogenous Moho vicinity is the rule rather than the exception for Andean-type orogens.